Vaginal myxoma in a Kathiawari horse. (25th December 2016) - Venkataramanan, R.; Sreekumar, C.; Krishnakumar, S.; Anil Kumar, R.; Selvaraj, J.
Summary: This case report describes a rare case of vaginal myxoma in a Kathiawari mare. The tumour, located on the left lateral vaginal wall, measured approximately 20 cm in diameter and resulted in dysuria, inappetance and loss of condition of the animal. Surgical enucleation of the tumour via a vaginal approach resulted in uneventful recovery of the horse. Based on the gross and histopathological observations, the tumour was diagnosed as a myxoma.